Mixed mode-I/II fatigue performance of Cement Emulsified Asphalt Mortar: Experimental and statistical analysis at intermediate temperature. (3rd October 2022) - Najjar, Shima; Mohammadzadeh Moghaddam, Abolfazl; Sahaf, Ali; Aliha, M.R.M.
Highlights: Fatigue life of CEAM with different mix designs under mixed-mode I/II loadings at three frequencies were investigated. Several mix designs with different cement contents, asphalt-to-cement ratios, and water-to-cement ratios were created. Dynamic tests on the SCB specimens were analyzed using the d -optimal response surface method. Cement content and asphalt-to-cement ratio have the greatest effect on the fatigue life in all mixed tensile-shear loadings. CEAM showed a longer fatigue life under dynamic loading in the pure shear mode. Increasing the loading frequency increased the fatigue life of the mortar in all three modes. Abstract: This study has investigated fatigue life of Cement Emulsified Asphalt Mortar (CEAM) under mixed-mode I/II loadings at the intermediate temperature. For this investigation, SCB specimens of 16 randomized mixture designs with different cement contents (C), asphalt-to-cement ratios (A/C), and water-to-cement ratios (W/C) were prepared and subjected to the cyclic mixed tensile-shear loading with M e = 0, 0.5, 1.0 at three frequencies of 2, 4 and 8 Hz. The results were analyzed using the d -optimal response surface method and revealed that for all three loading modes, the fatigue life increased with increasing C and A/C. The CEAM also showed a longer fatigue life in the pure shear mode than in the pure tensile mode. The difference between the fatigue life of mode I and II was found to be increasing with the increase in cement content and loading frequency. Increasing the loading frequency increased the fatigue life of the mortar in all three modes.